(untitled) (Revista Innova Educación, 2022)
he general objective of the research was to determine the relationship between executive functions and psychological well-being of first-year high school students from an educational institution in Callao. The study was carried out through an empirical, correlational-simple methodological design. The participants were 216 high school students from an educational institution in the Constitutional Province of Callao. The technique was the survey and the instruments were the EFECO questionnaire and psychological well-being scale (BIPSI). The results have shown that there is a significant relationship between executive functions and psychological well-being, concluding that executive functions are the cognitive capacities of the prefrontal cortex that allow self-regulatory behaviors, self-determine actions, socialize, develop a life purpose and have autonomy. In conclusion: there was a significant and direct relationship between executive functions and psychological well-being of first-year high school students from an educational institution in Callao.